Discovery of Tick-Borne Karshi Virus Implies Misinterpretation of the Tick-Borne Encephalitis Virus Seroprevalence in Northwest China - Bai, Yuan; Zhang, Yanfang; Su, Zhengyuan; Tang, Shuang; Wang, Jun; Wu, Qiaoli; Yang, Juan; Moming, Abulimiti; Zhang, Yujiang; Bell-Sakyi, Lesley; Sun, Surong; Shen, Shu; et al. (Frontiers in Microbiology, 2022)
Despite few human cases of tick-borne encephalitis virus (TBEV), high rates of TBEV seroprevalence were reported among humans and animals in Xinjiang Uygur Autonomous Region in Northwestern China. In this study, the Karshi virus (KSIV) was identified and isolated from Hyalomma asiaticum ticks in Xinjiang. It belongs to the genus Flavivirus of the family Flaviviridae and is closely related to TBEV. KSIV infects cell lines from humans, other mammals and ticks, and causes encephalitis in suckling mice. High minimum infection rates (4.96%) with KSIV were detected among tick groups. KSIV infections have occurred in sheep and marmots, resulting in antibody-positive rates of 2.43% and 2.56% respectively. We further found that, of the KSIV antibody-positive serum samples from animals, 13.9% had TBEV exposure showing cross-reaction to KSIV, and 11.1% had KSIV infection resulting in cross-reaction to TBEV; 8.3% were likely to have co-exposure to both viruses (or may be infected with one of them and present cross-reactivity with the other). The results revealed a substantial KSIV prevalence among ticks in Xinjiang, indicating exposure of animals to KSIV and TBEV. The findings implied misinterpretation of the high rates of TBEV seroprevalence among humans and animals in previous studies. There is a need to develop detection methods to distinguish KSIV from TBEV and to perform an in-depth investigation of KSIV and TBEV prevalence and incidence in Northwestern China, which would enhance our preparation to provide medical treatment of emerging diseases caused by tick-borne viral pathogens such as KSIV.